Acceleration of post-tooth extraction socket healing after continuous aerobic and anaerobic physical exercise in Wistar rats (Rattus norvegicus) - Aqsa Sjuhada Oki; Moch Febi Alviansyah; Christian Khoswanto; Retno Pudji Rahayu; Muhammad Luthfi (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Physical exercise has been proven to accelerate wound healing. Physical training itself consists of aerobic (continuous training) and anaerobic (interval training) exercise. The effectiveness of continuous physical exercise on post-tooth extraction wound healing is the focus of this study. Purpose: This study aims to investigate the differences in post-tooth extraction wound healing in Wistar rats (Rattus norvegicus) after aerobic and anaerobic exercise based on the number of fibroblasts and neovascularisation. Methods: Wistar rats were divided into three groups: the control group (K1); K2 undertook continuous aerobic exercise, swimming at 50% maximum swimming capacity (MSC) with an additional 3% bodyweight load; K3 undertook anaerobic continuous exercise, swimming at 65% MSC with a 6% load. The rats swam three times per week for six weeks. The number of fibroblasts and neovascularisation were examined three days after tooth extraction. Data was analysed using the one-way analysis of variance (ANOVA) and Least Significant Difference (LSD) tests (p<0.05). Results: There was a significant difference in the number of fibroblasts between the K2 and K3 groups. There was no significant difference between K2 and K3 in the amount of neovascularisation. Conclusion: There were differences in the number of fibroblasts but not neovascularisation after tooth extraction in Wistar rats given aerobic and anaerobic continuous training.